Efecto del ácido giberélico y escarificación sobre la germinación de semillas y el crecimiento inicial en Chirimoya (Annona cherimola L.) - Achupallas España, Roberto Patricio (2019)
The germination percentage of Annona Cherimola Mill. Is 20%, with a germination time from 90 days to 900 days after planting according to the environmental conditions where it is grown. The seed has a hardened coverage little permeable causing morphological and morphophysiological latency; to this it is added that in our country there are no studies on pre-germination of custard apple due to it is not considered as a crop with economic importance. Unlike Spain, Israel, Chile and other countries where custard apple is grown intensively due to the important economic incomes. For these reasons, the current research presents the effect of scarification and dose of gibberellin on the germination and initial growth of endemic seeds of custard apple carried in the province of Loja, in order to break the dormancy of the seeds and obtain an affective germination percentage. It evaluates three levels of scarification: without scarification, sanding of the seed coverage and cutting of the seed base, with four levels of gibberellin: 0 ppm, 100 ppm, 500 ppm and 1200 ppm, with a bifactorial arrangement with twelve treatments and ten repetitions per treatment. The trial was established in the parish of Malacatos, San José neighborhood. For ANOVA, the Infostat software version 2018 was used. The best results in germination and initial growth of treatments T9 and T8 with 500 ppm of gibberellin and scarification of sanding coverage with sand and cutting of the base of the seed, with germinative percentages of 96% and 94% respectively; it presented in both cases an interaction between gibberellin and scarification, compared with the control which had 0 ppm of gibberellin and, without scarification with a percentage of 29%. Finally, the treatment with the lowest germination percentage was T11 with 1200 ppm of gibberellin and the cutting of the base of the seed with a percentage of 20%. In this way, it is concluded that gibberellins play a decisive role in germination and with the help of scarification mechanisms can greatly enhance the germination and initial growth of custard apple for the use of the fruit grower.